PENGARUH PERAMBATAN HUTAN TERHADAP ASPEK HIDROLOGI - hasbi arbi, hasbi hasbi (JURNAL LENTERA, 2012)
The purpose Water Resourse Depelopment used for controller and useful of water, where water controle used for to cotroling float water and normal volume, but water can be used  for domestic water. Industtri, irigation, water tranfortation and water strength for run up electric mechines. To use of water shuld be have more water with the volume of water is relative  counstan  and sustainable, it can be happened if the support factor  suck us porest  and river can be protected  and  continue, so water resource  can be enough and  controlled.             The forest  is the best controle  of rain water, until the rain water infilt into the ground can be more end runoff water is less, until porest can stop soil erosion. Ilegal forest couse the land / soil criyical condision end barren of land, until runoff water can be biggest and infitrasi will be less, finally ground water will be little, this couse at dryseasion river water will be less/dryness, until water river does not useful for sustainable. At wet seasion  runoff water  sweep away soil particle of soil erosion by rain to the rivers until the river base will be slope slightly, this be coused the rivers overflow, finally couse flood water , finally couse  that  soil pertility less, because the  soil surfase erosion by rain water couse the porest bald and nonarable . this couse new plans can not grow again. This problem can be protected if  local goverment implant  forect and land conservation by reforestasion or planting new porest at the rigional place, finally  misfortune ftoodwater and dryness can be preventatived.